Lithium secondary battery

By adding specific additive combinations to the non-aqueous electrolyte solution of the lithium secondary battery, a solid SEI film is formed, which solves the problem of degradation of the performance of the lithium secondary battery under high temperature conditions, and significantly improves the high temperature life and gas generation amount of the battery.

CN119452494APending Publication Date: 2025-02-14LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380050377.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-05
Filing Date
2023-07-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When the lithium secondary battery is driven under high temperature conditions, the thermal decomposition product of the lithium salt in the electrolyte solution causes membrane damage and the dissolution of transition metal ions, thereby reducing battery performance.

Method used

The nonaqueous electrolyte solution containing a combination of two specific additives is introduced. The first additive forms a poly(ethylene oxide)-type SEI film through free radical reaction, and the second additive forms a polyphosphate-type SEI film through ring opening reaction to enhance the negative electrode. high temperature durability and inhibit HF generation.

Benefits of technology

Improve the gas production amount and life of lithium secondary batteries at high temperatures, prevent transition metal electrodeposition and film damage, and maintain excellent battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213588870000021
    Figure BDA0005213588870000021
  • Figure BDA0005213588870000022
    Figure BDA0005213588870000022
  • Figure BDA0005213588870000031
    Figure BDA0005213588870000031
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery comprising: a non-aqueous electrolyte solution containing a lithium salt, an organic solvent, a first additive represented by formula 1, and a second additive represented by formula 2; a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material composed of silicon; and a separator disposed between the positive electrode and the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority of Korean Patent Application No. 10-2022-0087179 filed on July 14, 2022, and Korean Patent Application No. 10-2023-0087210 filed on July 5, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein. Technical Field

[0003] The invention relates to a lithium secondary battery, which comprises an electrolyte solution containing a specific additive combination and a pure silicon (pure Si) negative electrode material. Background Art

[0004] Lithium secondary batteries are generally prepared by the following method: a separator is arranged between the positive electrode and the negative electrode to form an electrode assembly, and then the electrode assembly is inserted into a battery shell, the positive electrode contains a positive electrode active material formed of a lithium-containing transition metal oxide, and the negative electrode contains a negative electrode active material capable of storing lithium ions; a non-aqueous electrolyte solution as a lithium ion transmission medium is injected therein, and then the battery shell is sealed.

[0005] Since lithium secondary batteries can be miniaturized and have high energy density and operating voltage, they are being used in various fields including mobile devices, electronic products, and electric vehicles, etc. As the application fields of lithium secondary batteries are diversified, the physical property conditions required for lithium secondary batteries are also gradually increasing, and specifically, there is a need to develop lithium secondary batteries that can be stably driven even under high temperature conditions.

[0006] Meanwhile, when the lithium secondary battery is driven under high temperature conditions, PF6 can be thermally decomposed from the lithium salt (such as LiPF6) contained in the electrolyte solution. - Anions are generated, thereby generating Lewis acids (such as PF5), which can react with moisture to generate HF. The decomposition products (such as PF5 and HF) can not only destroy the film formed on the electrode surface, but also cause a decomposition reaction of the organic solvent, and can react with the decomposition products of the positive electrode active material to dissolve the transition metal ions, and the dissolved transition metal ions can be electrodeposited on the negative electrode to destroy the film formed on the negative electrode surface.

[0007] If the above-mentioned electrolyte decomposition reaction continues on the damaged membrane, the performance of the battery will further decrease, so it is necessary to develop a secondary battery that can maintain excellent performance even under high temperature conditions. Summary of the invention

[0008] [Technical issues]

[0009] The present invention aims to improve the high temperature performance of lithium secondary batteries containing pure silicon negative electrode active materials by introducing a non-aqueous electrolyte solution containing a combination of two specific additives.

[0010] [Technical solution]

[0011] According to one aspect of the present invention, a lithium secondary battery is provided, comprising: a non-aqueous electrolyte solution containing a lithium salt, an organic solvent, a first additive represented by the following chemical formula 1, and a second additive represented by the following chemical formula 2; a positive electrode comprising a positive electrode active material; a negative electrode comprising a negative electrode active material composed of silicon; and a separator arranged between the positive electrode and the negative electrode.

[0012] [Formula 1]

[0013]

[0014] In the above Formula 1, A is a heterocyclic group having 3 to 5 carbon atoms or a heteroaryl group having 3 to 5 carbon atoms, and R1 is an alkylene group having 1 to 3 carbon atoms.

[0015] [Formula 2]

[0016]

[0017] In Formula 2 above, R2 is an alkyl group having 1 to 10 carbon atoms substituted with one or more fluorine groups.

[0018] [Beneficial Effects]

[0019] The lithium secondary battery of the present invention includes a non-aqueous electrolyte solution containing a specific additive combination, and thus can improve the high temperature life and gas generation amount of the lithium secondary battery including a silicon negative electrode active material. DETAILED DESCRIPTION

[0020] Hereinafter, the present invention will be described in more detail.

[0021] Generally, lithium salts, such as LiPF6, which is widely used in lithium secondary battery electrolytes, contain anions that can form decomposition products such as hydrogen fluoride (HF) and PF5 due to thermal decomposition or moisture, which is exacerbated when driven under high temperature conditions. These decomposition products have acidic properties and thus deteriorate the surface properties of the electrodes in the battery.

[0022] Due to the decomposition products of the electrolyte solution and the changes in the positive electrode structure caused by repeated charging and discharging, the transition metal in the positive electrode is easily dissolved into the electrolyte solution, and the dissolved transition metal will be redeposited on the positive electrode to increase the resistance of the positive electrode.

[0023] In addition, in the case where the dissolved transition metal moves to the negative electrode through the electrolyte solution, the dissolved transition metal is electrodeposited on the negative electrode to cause destruction of the solid electrolyte interphase (SEI) film and additional electrolyte decomposition reaction, resulting in problems such as lithium ion consumption and increased resistance.

[0024] In particular, when silicon (Si) is used as a negative electrode active material, due to the large volume change during charge / discharge, the SEI film is easily destroyed and then regenerated, and such reactions occur continuously. As a result, there are problems of battery durability degradation and increased gas generation.

[0025] In order to solve this problem, the present inventors have included a first additive represented by Formula 1 below and a second additive represented by Formula 2 below in a non-aqueous electrolyte solution, and found that a strong SEI film is formed on the negative electrode, thereby improving the performance of the battery, especially the gas generation amount at high temperature.

[0026] Hereinafter, each component constituting the present invention will be described in more detail.

[0027] Non-aqueous electrolyte solution

[0028] The lithium secondary battery of the present invention includes a non-aqueous electrolyte solution containing a lithium salt, an organic solvent, a first additive represented by the following Chemical Formula 1, and a second additive represented by the following Chemical Formula 2.

[0029] Hereinafter, each component of the nonaqueous electrolyte solution will be described in detail.

[0030] (1) First additive and second additive

[0031] The nonaqueous electrolyte solution of the present invention includes a first additive represented by Formula 1 below.

[0032] [Formula 1]

[0033]

[0034] In the above Formula 1, A is a heterocyclic group having 3 to 5 carbon atoms or a heteroaryl group having 3 to 5 carbon atoms, and R1 is an alkylene group having 1 to 3 carbon atoms.

[0035] Since the first additive represented by the above formula 1 contains a propargyl functional group, when the first additive is contained in the electrolyte solution, the first additive is reduced and decomposed by a free radical reaction, thereby forming a SEI film having a poly(ethylene oxide) (PEO)-based polymer component on the surface of the negative electrode. Therefore, the high temperature durability of the negative electrode itself can be improved, and the electrodeposition of transition metals on the surface of the negative electrode can also be prevented. In addition, the propargyl group has the property of being adsorbed on metal ions, and therefore, the function of preventing impurities from being eluted can be exerted by adsorbing on the surface of the metal impurities contained in the positive electrode, and the function of suppressing internal short circuits can be exerted by preventing the eluted metal ions from being precipitated on the negative electrode. In addition, the first additive is compounded with PF5 (a decomposition product of the electrolyte solution), thereby suppressing the generation of HF, and therefore, the destruction of the positive electrode electrolyte interface phase (CEI) film formed on the surface of the positive electrode can also be prevented, and further decomposition of the electrolyte solution can be suppressed.

[0036] In an embodiment of the present invention, A of the above Formula 2 may be a nitrogen-containing heteroaryl group having 3 to 5 carbon atoms.

[0037] As a preferred example, the first additive may be represented by the following Formula 1-1.

[0038] [Formula 1-1]

[0039]

[0040] In the above formula 1-1, R1 is the same as defined in formula 1.

[0041] In an embodiment of the present invention, R1 in the above Formula 1 may be a linear or branched alkylene group having 1 to 3 carbon atoms, preferably a linear alkylene group having 1 to 3 carbon atoms, and more preferably a methylene group.

[0042] As a preferred example, the first additive may be represented by the following Formula 1A.

[0043] [Formula 1A]

[0044]

[0045] In an embodiment of the present invention, the content of the first additive may be 0.05 wt % to 10 wt %, preferably 0.1 wt % to 1 wt %, and more preferably 0.1 wt % to 0.5 wt %, based on the total weight of the nonaqueous electrolyte solution. Considering that when the content of the first additive is too much, the first additive may excessively participate in the decomposition reaction at the interface between the electrode and the electrolyte solution, and the membrane resistance may become too large, thereby causing the problem of increased battery resistance, it is preferred that the content of the first additive is 10 wt % or less.

[0046] Furthermore, the nonaqueous electrolyte solution of the present invention includes a second additive represented by Formula 2 below.

[0047] [Formula 2]

[0048]

[0049] In Formula 2 above, R2 is an alkyl group having 1 to 10 carbon atoms substituted with one or more fluorine groups.

[0050] The second additive represented by Formula 2 above includes a cyclic phosphate structure, so when included in the electrolyte solution, a SEI film having a polyphosphate (PPE) component can be formed on the surface of the negative electrode by a ring-opening reaction, which can give the silicon negative electrode elasticity. That is, due to the enhanced durability to the volume change of silicon, the negative electrode can be prevented from deteriorating in a cycle and high temperature environment. In addition, the second additive includes a fluoroalkyl group, so that an inorganic SEI film based on LiF can be formed on the positive and negative electrodes by reacting with lithium ions. Since LiF has physically strong properties and is compatible with lithiated silicon (Li x Si) has a strong bonding property and thus has the effect of suppressing battery degradation caused by reactions between the electrolyte and electrode interface.

[0051] In one embodiment of the present invention, R2 of the above formula 2 may be -(CR2) n CF3, R may be hydrogen or fluorine, and n may be an integer from 0 to 9. Preferably, R2 of the above formula 2 may be -(CH2) n CF3, and n may be an integer from 0 to 5, and more preferably, n may be an integer from 1 to 3.

[0052] As a preferred example, the second additive may be represented by the following Formula 2A.

[0053] [Formula 2A]

[0054]

[0055] In an embodiment of the present invention, the second additive may be included in an amount of 0.1 wt % to 15 wt % based on the total weight of the nonaqueous electrolyte solution.

[0056] Specifically, based on the total weight of the non-aqueous electrolyte solution, the content of the second additive may be 0.5 wt % or more, preferably 2 wt % or more, more preferably 5 wt % or more, and most preferably 10 wt % or more. However, considering the fact that the resistance of the battery may increase due to the decomposition of the second additive when the second additive is added in excess, it is preferred that the content of the second additive is 15 wt % or less.

[0057] In the non-aqueous electrolyte solution of the present invention, when the first additive and the second additive are used together, the A substituent of Formula 1, specifically the lone electron pair present in imidazole, further promotes the ring-opening reaction of Formula 2 of the second additive, so that the reduction reaction can occur smoothly with less energy. As a result, when the SEI layer is formed on the silicon negative electrode, the polymer film component can be further increased, and the generation of HF can be suppressed by chelating PF5. In particular, in the case of Si negative electrode materials, due to the large volume change, the phenomenon of film damage and durability degradation caused by HF in a high temperature environment is aggravated, so through the combination of the above additives, the effect of improving durability and reducing gas generation can be more significant.

[0058] In an embodiment of the present invention, the weight ratio of the second additive to the first additive in the non-aqueous electrolyte solution, that is, the ratio of the weight of the second additive (W2) to the weight of the first additive (W1) (W2 / W1), may be 1.5 or more, preferably 6 or more, more preferably 16 or more, and most preferably 30 or more. When the relative ratio of the second additive increases, it is advantageous to form a polymer film due to the ring-opening reaction of the cyclic phosphate structure. In addition, LiF formed by the recombination of -CF3 and lithium ions can be used to enhance the durability of the film, making it preferred in improving the high temperature performance of batteries using pure Si as negative electrodes. However, considering the fact that when a film having a polymer component is formed too thick due to the decomposition of an excessive amount of the additive, the battery resistance increases, and side reactions and by-products are caused during the decomposition process, it is preferred that the weight ratio of the second additive to the first additive is 40 or less.

[0059] (2) Third additive

[0060] The nonaqueous electrolyte may include any one or more compounds selected from the group consisting of cyclic carbonate compounds, sultone compounds, sulfate compounds, phosphorus compounds, nitrile compounds, amine compounds, silane compounds, benzene compounds and lithium salt compounds as the third additive.

[0061] The cyclic carbonate-based compound may be any one or more selected from vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate (FEC), and may specifically be vinylene carbonate.

[0062] The sultone compound is a material that can form a stable SEI film on the surface of the negative electrode through a reduction reaction, and can be any one or more selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethylene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone and 1-methyl-1,3-propene sultone, and can specifically be 1,3-propane sultone (PS).

[0063] The sulfate / ester compound is a material that can undergo electrolysis on the surface of the negative electrode to form a stable SEI film that does not break even during high-temperature storage, and can be any one or more of ethylene sulfate (Esa), trimethylene sulfate (TMS) or methyl trimethylene sulfate (MTMS).

[0064] The phosphorus compound may be a phosphate or phosphite compound, and specifically, may be any one or more selected from the group consisting of tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate and tris(trifluoroethyl)phosphite.

[0065] The nitrile compound can be any one or more selected from the group consisting of succinonitrile (SN), adiponitrile (ADN), acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzylacetonitrile, 2-fluorobenzeneacetonitrile, 4-fluorobenzeneacetonitrile, ethylene glycol bis(2-cyanoethyl) ether (ASA3), 1,3,6-hexanetricarboxylate (HTCN), 1,4-dicyano-2-butene (DCB) and 1,2,3-tris(2-cyanoethyl)propane (TCEP).

[0066] The amine compound may be any one or more of triethanolamine and ethylenediamine, and the silane compound may be tetravinylsilane.

[0067] The benzene compound may be any one or more selected from the group consisting of monofluorobenzene, difluorobenzene, trifluorobenzene and tetrafluorobenzene.

[0068] The lithium salt compound is a compound different from the lithium salt contained in the non-aqueous electrolyte solution, and can be any one or more selected from the group consisting of lithium difluorophosphate (LiDFP; LiPO2F2), lithium bis(oxalato)borate (LiBOB; LiB(C2O4)2), lithium tetrafluoroborate (LiBF4), lithium tetraphenylborate and lithium difluorobis(oxalato)phosphate (LiDFOP).

[0069] Preferably, the non-aqueous electrolyte solution of an embodiment of the present invention may further include any one or more third additives selected from the group consisting of vinylene carbonate (VC), 1,3-propane sultone (PS), 1,3-propylene sultone (PRS) and lithium difluorophosphate (LiDFP). In this case, since a stronger SEI layer can be formed on the surface of the negative electrode during the initial activation of the secondary battery, gas generation due to decomposition of the electrolyte at high temperature is suppressed, and the resistance increase rate with increasing cycles during the driving process of the battery can be reduced.

[0070] In an embodiment of the present invention, the content of the third additive may be 0.05 wt % to 5 wt %, preferably 0.1 wt % to 3 wt % based on the total weight of the nonaqueous electrolyte solution. In terms of reducing initial resistance, the content of the third additive is preferably 5 wt % or less.

[0071] (3) Organic solvents

[0072] The nonaqueous electrolyte solution of the present invention includes an organic solvent.

[0073] The various organic solvents that are usually used in lithium electrolytes can be used as organic solvents without restriction. For example, the organic solvent can be a cyclic carbonate solvent, a linear carbonate solvent, a linear ester solvent, a cyclic ester solvent, a nitrile solvent or a mixture thereof, can preferably include a mixture of a cyclic carbonate solvent and a linear carbonate solvent, and can more preferably include a mixture of a fluorinated cyclic carbonate solvent and a linear carbonate solvent.

[0074] The cyclic carbonate organic solvent is a high viscosity organic solvent, which can dissociate the lithium salt in the electrolyte well due to its high dielectric constant, and can be at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate and vinylene carbonate, and preferably can include fluoroethylene carbonate (FEC). When a fluorinated cyclic carbonate solvent (such as FEC) is used, an inorganic SEI layer based on LiF can be formed, thereby having the advantage of being able to form a hybrid film together with the polymer component organic film formed by the additive.

[0075] In addition, linear carbonate solvent is an organic solvent of low viscosity and low dielectric constant, it can be any one or more of the group selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, can preferably include diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or its mixture, can more preferably include diethyl carbonate and ethyl methyl carbonate. Although DMC is an organic solvent that effectively increases ionic conductivity and improves room temperature resistance, when DMC is used as linear carbonate solvent alone, DMC is unstable at high temperatures, so the shortcoming is that the gas formation caused by reduction reaction increases, and causes low temperature performance to significantly reduce due to high freezing point. Therefore, in reducing gas generation, improving the durability of the film formed on the electrode and improving the low temperature performance of the battery, preferably use DEC, EMC or its combination. Especially, EMC has a viscosity lower than DEC, is therefore favourable in improving ionic conductivity.

[0076] The chain ester solvent may be any one or more selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate and butyl propionate, and may preferably be methyl propionate, ethyl propionate or propyl propionate.

[0077] The cyclic ester solvent may be any one or more selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.

[0078] The nitrile solvent may be any one or more selected from the group consisting of succinonitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl cyanide and 4-fluorophenyl cyanide, and may preferably be succinonitrile.

[0079] Unless otherwise specified, the portion other than the content of other components other than the organic solvent (eg, the content of the first to third additives and the lithium salt) in the total weight of the nonaqueous electrolyte solution may all be the organic solvent.

[0080] (4) Lithium salt

[0081] The nonaqueous electrolyte solution of the present invention includes a lithium salt.

[0082] Any lithium salt generally used in an electrolyte solution for a lithium secondary battery may be used as the lithium salt without limitation, and specifically, the lithium salt may include Li + as a cation, and may include a - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4- , BC4O8 - 、BF2C2O4CHF - PF4C2O4 - PF2C4O8 - PO2F2 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - Any one or more of the following can be used as anions.

[0083] Specifically, the lithium salt can be any one or more selected from the group consisting of LiPF6, LiClO4, LiBF4, lithium bis(fluorosulfonyl)imide (LiN(FSO2)2; LiFSI), LiTFSI, lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), LiSO3CF3, LiPO2F2, lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LiFOB), lithium difluoro(bisoxalate)phosphate (LiDFOP), lithium tetrafluoro(oxalate)phosphate (LiTFOP) and lithium fluoromalonate (difluoro)borate (LiFMDFB), and can preferably be LiPF6.

[0084] In one embodiment of the present invention, the concentration of the lithium salt in the non-aqueous organic solution containing the lithium salt and the organic solvent (i.e., a mixed solution of the lithium salt and the organic solvent) may be 0.5 M or more, specifically 1.0 M or more, and more specifically 1.5 M or more. When the concentration of the lithium salt is within the above range, the effects of improving low-temperature output and improving cycle characteristics can be fully ensured, and in particular, when the concentration of the lithium salt is as high as 1.5 M or more, the degree of participation of anions in the lithium ion solvation shell in the electrolyte can be increased. Therefore, by the anions in the lithium salt (e.g., PF6 - ) Adding an inorganic component (such as LiF) to the negative electrode SEI layer makes it possible to enhance the durability against volume changes of the silicon negative electrode. At the same time, in order to prevent excessive increases in viscosity and surface tension to obtain appropriate electrolyte wettability, the concentration of the lithium salt is preferably 4.0M or less, specifically 3.0M or less, and more specifically 2.0M or less.

[0085] positive electrode

[0086] The positive electrode of the present invention includes a positive electrode active material, and may be prepared by coating a positive electrode collector with a positive electrode slurry including the positive electrode active material, a binder, a conductive material, and a solvent, followed by drying and roll-pressing.

[0087] The positive electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium or silver can be used.

[0088] The positive electrode active material is a compound that can reversibly insert and deinsert lithium, and can be any one or more selected from the group consisting of LCO (LiCoO2), LNO (LiNiO2), LMO (LiMnO2), LiMn2O4, LiCoPO4, LFP (LiFePO4) and lithium composite transition metal oxides containing nickel (Ni), cobalt (Co) and manganese (Mn).

[0089] Meanwhile, the positive electrode active material may be a lithium composite transition metal oxide in which the molar ratio of nickel in the transition metal is 70 mol % or more, preferably 80 mol % or more, and more preferably 85 mol % or more.

[0090] The high Ni type positive active material having a nickel content of 70 mol% or more in the total transition metal is structurally unstable, so that the positive active material may collapse and crack at high temperatures. In the case where the active material collapses as described above, the surface area increases, thereby increasing the sites where side reactions can occur with the electrolyte, and as a result, a large amount of gas is generated when exposed to high temperatures. When gas is continuously generated as described above, the internal pressure of the battery increases, resulting in exhaust at an early stage and stopping the operation of the battery before the end of the battery life, so it is important to solve such side reaction problems and gas generation problems, which can be solved by the non-aqueous electrolyte solution comprising the first additive and the second additive of the present invention to enhance film formation.

[0091] In an embodiment of the present invention, the lithium composite transition metal oxide may be a compound represented by the following Formula 3. That is, the positive electrode active material according to an embodiment of the present invention may include the lithium composite transition metal oxide represented by the following Chemical Formula 3.

[0092] [Formula 3]

[0093] Li 1+x (Ni a Co b Mn c M d )O2

[0094] In Formula 3 above, M is any one or more selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,

[0095] 1 + x, a, b, c, and d are the atomic fractions of each independent element, where -0.2 ≤ x ≤ 0.2, 0.60 ≤ a < 1, 0 < b ≤ 0.30, 0 < c ≤ 0.30, 0 ≤ d ≤ 0.10, and a + b + c + d = 1.

[0096] 1 + x represents the molar ratio of lithium in the lithium composite transition metal oxide, where x can satisfy -0.1 ≤ x ≤ 0.2 or 0 ≤ x ≤ 0.2. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium composite transition metal oxide can be formed stably.

[0097] a represents the molar ratio of nickel in all metals other than lithium in the lithium composite transition metal oxide, where a can satisfy 0.70 ≤ a < 1, 0.80 ≤ a < 1, 0.85 ≤ a < 1. When the molar ratio of nickel satisfies the above range, high capacity can be achieved because high energy density can be exhibited.

[0098] b represents the molar ratio of cobalt in all metals other than lithium in the lithium composite transition metal oxide, where b can satisfy 0 < b ≤ 0.20, 0 < b ≤ 0.15, or 0 < b ≤ 0.10. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be achieved.

[0099] c represents the molar ratio of manganese in all metals other than lithium in the lithium composite transition metal oxide, where c can satisfy 0 < c ≤ 0.20, 0 < c ≤ 0.15, or 0 < c ≤ 0.10. When the molar ratio of manganese satisfies the above range, the structural stability of the positive electrode active material is excellent.

[0100] In an embodiment of the present invention, the lithium composite transition metal oxide may include at least one doping element selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and may preferably include Al as the doping element. In other words, d representing the molar ratio of the doping element in all metals other than lithium in the lithium composite transition metal oxide can satisfy 0 < d ≤ 0.10, 0 < d ≤ 0.08, 0 < d ≤ 0.05.

[0101] Preferably, a, b, c, and d in Formula 3 above may be 0.70 ≤ a < 1, 0 < b ≤ 0.20, 0 < c ≤ 0.20, and 0 ≤ d ≤ 0.10, respectively.

[0102] The content of the positive electrode active material may be 80 wt % to 99 wt %, specifically 90 wt % to 99 wt %, based on the total weight of the solid in the positive electrode slurry. When the amount of the positive electrode active material is 80 wt % or less, the energy density may be reduced, and thus the capacity may be reduced.

[0103] The binder is a component that helps the bonding between the active material and the conductive material and the bonding with the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solids in the positive electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0104] In addition, the conductive material is a material that provides conductivity without causing chemical changes in the battery, and the conductive material may be added in an amount of 0.5 wt % to 20 wt % based on the total weight of the solids in the positive electrode slurry.

[0105] The conductive material can be selected from the following conductive materials, for example: carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as fluorocarbon powders, nickel powders and aluminum powders; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0106] In addition, the solvent of the positive electrode slurry may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and its amount may be such that a preferred viscosity is obtained when the positive electrode active material, the binder and the conductive material are included. For example, the content of the solvent may be such that the solid concentration in the positive electrode slurry including the positive electrode active material, the binder and the conductive material is 40 wt % to 90 wt %, preferably 50 wt % to 80 wt %.

[0107] negative electrode

[0108] The lithium secondary battery of the present invention includes a negative electrode including a negative electrode active material, and the negative electrode can be prepared by coating a negative electrode collector with a negative electrode slurry including a negative electrode active material, a binder, a conductive material, a solvent, etc., followed by drying and roll pressing.

[0109] The negative electrode current collector generally has a thickness of 3 μm to 500 μm. The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy can be used. In addition, similar to the positive electrode current collector, tiny irregularities may be formed on the surface of the negative electrode current collector to improve the adhesion of the negative electrode active material. The negative electrode current collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0110] In the present invention, the negative electrode active material is composed of silicon (Si). As a negative electrode active material, the theoretical capacity of silicon is about 10 times that of graphite, making it possible to realize a high-capacity battery and also to reduce the mass load (mg·cm -2 ) to improve the fast charging performance of the battery. However, the problem is that the lithium ion loss rate caused by the irreversible reaction is high and the volume change is large, which may adversely affect the lifespan, and in particular, in the case of a 100% Si negative electrode, the following phenomenon is aggravated: due to the large volume change during the charge / discharge process, the SEI film is easily damaged and then regenerated, and this reaction occurs continuously. However, when the non-aqueous electrolyte solution of the present invention is applied, the SEI film as described above can be strengthened, so that the above-mentioned problems can be effectively solved.

[0111] The negative electrode active material may be contained in an amount of 60 wt % to 99 wt % based on the total weight of solids in the negative electrode slurry.

[0112] The binder is a component that helps the bonding between the conductive material, the active material and the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solids in the negative electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber and various copolymers thereof.

[0113] The conductive material is a component for further improving the conductivity of the negative electrode active material, wherein the conductive material may be added in an amount of 0.5 wt % to 20 wt % based on the total weight of the solid in the negative electrode slurry. Any conductive agent may be used without particular limitation, as long as it has conductivity and does not cause chemical changes in the battery, for example: carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes, or graphite with a very developed crystal structure; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive materials such as polyphenylene derivatives; or combinations thereof.

[0114] The solvent of the negative electrode slurry may include water or an organic solvent such as NMP and alcohol, and its amount may be such that a preferred viscosity is obtained when including a negative electrode active material, a binder, a conductive material, etc. For example, the content of the solvent may be such that the solid concentration in the slurry including the negative electrode active material, the binder, and the conductive material is 20 wt % to 80 wt %, preferably 20 wt % to 40 wt %.

[0115] Diaphragm

[0116] The lithium secondary battery of the present invention includes a separator between a positive electrode and a negative electrode.

[0117] The separator separates the negative electrode and the positive electrode and provides a movement path for lithium ions, wherein any separator can be used as the separator without particular limitation as long as it is commonly used in lithium secondary batteries, and in particular, a separator having excellent electrolyte impregnation and safety and low resistance to the movement of electrolyte ions can be used.

[0118] Specifically, as a diaphragm, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure with more than two layers of the above-mentioned polymer can be used. Moreover, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated diaphragm including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a single layer or multilayer structure can be selectively used.

[0119] The lithium secondary battery of the present invention as described above can be suitably used in portable devices such as mobile phones, notebook computers, and digital cameras; and in the field of electric vehicles such as hybrid electric vehicles (HEVs).

[0120] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module are provided.

[0121] The battery module or battery pack may be used as a power source for at least one of the following medium and large-sized devices: a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0122] The shape of the lithium secondary battery of the present invention is not particularly limited, and a cylindrical shape using a can, a prismatic shape, a pouch shape, or a coin shape may be used.

[0123] The lithium secondary battery of the present invention can be used not only in a single battery used as a power source for small devices but also as a unit cell in a medium or large battery module including a plurality of single batteries.

[0124] Hereinafter, the present invention will be described in detail according to specific embodiments.

[0125] <Example>

[0126] Example 1

[0127] (Preparation of non-aqueous electrolyte solution)

[0128] Fluoroethylene carbonate (FEC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 10:45:45, and then LiPF6 was dissolved until the concentration in the mixture reached 1.5 M, thereby preparing a non-aqueous organic solution. 0.3 wt % of the compound represented by Formula 1A, 0.5 wt % of the compound represented by Formula 2A and the remaining amount of the non-aqueous organic solution were mixed to prepare a 100 wt % non-aqueous electrolyte solution.

[0129] (Manufacturing of lithium secondary batteries)

[0130] As the positive electrode active material, Li(Ni 0.85 Co 0.05 Mn 0.08 Al 0.02 )O2, carbon black as a conductive material and polyvinylidene fluoride as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 97.74:0.7:1.56 to prepare a positive electrode slurry (solid content 75.5 wt %). The positive electrode slurry was coated on a positive electrode current collector (Al film) with a thickness of 15 μm, dried and then rolled to manufacture a positive electrode.

[0131] Si particles (Wacker) with an average particle size of 5 μm as a negative electrode active material, styrene-butadiene rubber-carboxymethyl cellulose (SBR-CMC) as a binder, and carbon black as a conductive material were mixed in a weight ratio of 70:9.7:20.3 in distilled water as a solvent to prepare a negative electrode active material slurry with a solid content of 26.0 wt %. The negative electrode active material slurry was coated on a negative electrode current collector (Cu film) with a thickness of 15 μm, dried, and then rolled to manufacture a negative electrode.

[0132] The electrode assembly was manufactured by sequentially stacking a positive electrode, a polyolefin-based porous separator coated with inorganic particles (Al2O3), and a negative electrode.

[0133] The assembled electrode assembly was housed in a pouch-type battery case, and the prepared nonaqueous electrolyte solution was then injected therein, thereby manufacturing a lithium secondary battery.

[0134] Example 2

[0135] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the content of the compound represented by Formula 2A was changed to 2 wt % when the nonaqueous electrolyte solution was prepared.

[0136] Example 3

[0137] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the content of the compound represented by Formula 2A was changed to 5 wt % when the nonaqueous electrolyte solution was prepared.

[0138] Example 4

[0139] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the content of the compound represented by Formula 2A was changed to 10 wt % when the nonaqueous electrolyte solution was prepared.

[0140] Example 5

[0141] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the content of the compound represented by Formula 1A was changed to 10 wt % when the nonaqueous electrolyte solution was prepared.

[0142] Example 6

[0143] A lithium secondary battery was manufactured in the same manner as in Example 1, except that 2.5 wt % of vinylene carbonate (VC) was additionally added when the nonaqueous electrolyte solution was prepared.

[0144] Comparative Example 1

[0145] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the compound represented by Formula 1A and the compound represented by Formula 2A were not added when the nonaqueous electrolyte solution was prepared.

[0146] Comparative Example 2

[0147] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the compound represented by Formula 2A was not added when the nonaqueous electrolyte solution was prepared.

[0148] Comparative Example 3

[0149] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the compound represented by Formula 1A was not added when the nonaqueous electrolyte solution was prepared.

[0150] Comparative Example 4

[0151] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a compound represented by the following formula Z1 (5-ethynyl-1-methyl-1H-imidazole) was used instead of the compound represented by formula 1A when preparing the nonaqueous electrolyte solution.

[0152] [Formula Z1]

[0153]

[0154] Comparative Example 5

[0155] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a compound represented by the following formula Z2 (2-ethoxy-1,3,2-dioxaphospholane 2-oxide) was used instead of the compound represented by formula 2A when preparing the nonaqueous electrolyte solution.

[0156] [Formula Z2]

[0157]

[0158] Comparative Example 6-1

[0159] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a mixture of SiO and artificial graphite as negative electrode active materials (mixing weight ratio of 2:8), styrene-butadiene rubber-carboxymethyl cellulose (SBR-CMC) as a binder, carbon black as a conductive material, and sodium carboxymethyl cellulose (CMC) as a thickener were mixed in distilled water as a solvent at a weight ratio of 96.0:2.3:0.7:1 to prepare a negative electrode active material slurry, and the slurry was used instead of the slurry described in Example 1.

[0160] Comparative Example 6-2

[0161] A lithium secondary battery was manufactured in the same manner as in Comparative Example 6-1, except that the compound represented by Formula 2A was not added when the nonaqueous electrolyte solution was prepared.

[0162] Comparative Example 6-3

[0163] A lithium secondary battery was manufactured in the same manner as in Comparative Example 6-1, except that the compound represented by Formula 1A was not added when the nonaqueous electrolyte solution was prepared.

[0164] <Experimental example>

[0165] Experimental Example 1: Evaluation of gas generation after high temperature (45°C) cycling

[0166] The lithium secondary batteries manufactured in Examples 1 to 6 and Comparative Examples 1 to 5 and 6-1 to 6-3 were subjected to a formation process, and then constant current / constant voltage (CC / CV) charging (0.05C cutoff) was performed at 45°C at a rate of 1C to 4.2V, and constant current (CC) discharge was performed at a rate of 0.5C to 3.0V.

[0167] In addition, after 200 cycles, the charged battery was transferred to a charge / discharger at room temperature (25°C), and the gas collected in the bag was analyzed using a gas chromatography-thermal conductivity detector (GC-TCD), and the relative gas generation amount of each battery was calculated by setting the gas generation amount measured in Comparative Example 1 to 100%, and is shown in the following Table 1.

[0168] Experimental Example 2: Evaluation of gas generation after high temperature (60°C) storage

[0169] The lithium secondary batteries manufactured in Examples 1 to 6 and Comparative Examples 1 to 5 and 6-1 to 6-3 were subjected to a formation process and then charged to 4.2V at a rate of 0.33C under constant current / constant voltage conditions at 25°C (0.05C cutoff), thereby fully charging the battery to SOC 100%. The fully charged battery was stored at 60°C for 8 weeks and then transferred to a charge / discharger at room temperature (25°C), and the gas collected in the bag was analyzed using a gas chromatography-thermal conductivity detector (GC-TCD), and the relative gas generation of each battery was calculated by setting the gas generation measured in Comparative Example 1 to 100%, and is shown in Table 1 below.

[0170] [Table 1]

[0171]

[0172] The results of Table 1 above confirm that when the first additive and the second additive are included as electrolyte solution additives, the amount of gas generated can be effectively reduced after high temperature cycling and high temperature storage of a lithium secondary battery using 100 wt % Si as a negative electrode active material.

[0173] Specifically, in the case where the first additive or the second additive is used alone (Comparative Examples 2 to 3), it can be confirmed that the effect of reducing the amount of gas generated is not significant compared to the case where the first additive and the second additive are not included (Comparative Example 1). In addition, although the compound of formula Z1 used in Comparative Example 4 is a propargyl-substituted imidazole compound (used instead of the first additive of the present application), it can be confirmed that the effect of reducing the amount of gas generated is significantly reduced. In addition, although the compound of formula Z2 used in Comparative Example 5 is a cyclic phosphate compound like the second additive of the present application, the methyl group is located at the end (R2 of Formula 2) instead of the fluoroalkyl group, and it can be confirmed that the increase in membrane resistance is aggravated instead, thereby further increasing the amount of gas generated compared to Comparative Example 1 without the use of additives. The reason for this phenomenon is that although the fluoroalkyl group helps to include components with excellent durability and ionic conductivity (such as LiF) in the SEI layer, the methyl group only produces a polyolefin component that is not conductive and has poor durability. That is, a part of the SEI layer cannot withstand the volume expansion of the Si negative electrode and is lost, and in the lost part, another layer of membrane is continuously produced due to the electrolyte side reaction during the cycle, which aggravates the increase in membrane resistance.

[0174] Meanwhile, in the case of Comparative Example 6-1 using a mixture of SiO and graphite instead of Si as the negative electrode active material, the gas generation amount was greater than that of Example 1, and compared with Comparative Examples 6-2 and 6-3 using the first additive and the second additive separately, it can be confirmed that the effect of reducing the gas generation amount is not significant. Through Comparative Examples 6-1 to 6-3, it can be seen that the combination of the first additive and the second additive of the present invention has a particularly significant effect in improving the high-temperature gas generation amount in the battery containing the pure Si negative electrode active material.

[0175] In Examples 1 to 6, it was confirmed that the effect of reducing the amount of gas generation was most excellent in Examples 3 and 4 in which the weight ratio (W2 / W1) of the second additive to the first additive was 15 or more.

[0176] Experimental Example 3: Evaluation of capacity retention after high temperature (45°C) cycling

[0177] The lithium secondary batteries manufactured in Examples 1 to 6 and Comparative Examples 1 to 5 were subjected to a formation process, and then constant current / constant voltage (CC / CV) charging (0.05C cutoff) was performed at 45°C at a rate of 1C to 4.2V, and constant current (CC) discharge was performed at a rate of 0.5C to 3.0V.

[0178] Each time of the above charge / discharge was set as 1 cycle, and the same charge / discharge was repeated 200 times. The retention rate of the capacity after 200 cycles relative to the initial discharge capacity after 1 cycle was calculated, and the results are shown in Table 2 below.

[0179] [Table 2]

[0180]

[0181] The results in Table 1 above confirm that when the first additive and the second additive of the present application are included as electrolyte additives, the high temperature life of the lithium secondary battery using 100 wt % Si as the negative electrode active material can be effectively improved.

[0182] Specifically, it can be confirmed that the capacity retention rate is significantly improved compared to when the first additive and the second additive are not included (Comparative Example 1) and when the first additive or the second additive is used alone (Comparative Examples 2 and 3). In addition, although the compound represented by Formula Z1 used in Comparative Example 4 and the compound represented by Formula Z2 used in Comparative Example 5 have structures similar to those of the first additive and the second additive of the present invention, respectively, it can be confirmed that these compounds make the life performance worse.

[0183] In addition, among Examples 1 to 6, it was confirmed that the effect of improving the capacity retention ratio was most excellent in Examples 3 and 4 in which the weight ratio (W2 / W1) of the second additive to the first additive was 15 or more.

[0184] Experimental Example 4: Evaluation of fast charging performance

[0185] The lithium secondary batteries manufactured in Examples 1 to 6 and Comparative Examples 1 to 5 and 6-1 to 6-3 were subjected to a formation process, and then charged to 4.2V at a constant current / constant voltage (CC / CV) rate of 1C at 25°C (0.05C cut-off), and discharged to 3.0V at a constant current (CC) rate of 0.5C to measure the initial discharge capacity, initial resistance and initial volume of the battery. At this time, the volume was measured by the buoyancy method.

[0186] Next, the lithium secondary battery was set to a state of charge (SOC) of 15% and then charged at 25° C. while changing the C-rate according to the SOC state shown in Table 3 below, and a voltage curve was measured by checking the voltage value of each charging interval at intervals of 1 second.

[0187] [Table 3]

[0188] Charging time(sec) C-ratio (C) SOC15% to 95% 720 4.0

[0189] Thereafter, the termination condition is set using the voltage value of each interval obtained in each interval, and the charge amount when charged in the CC mode is recorded. Then, the battery is discharged again to 15% SOC in the CC mode of 0.33C.

[0190] The above-mentioned charge and discharge was set as 1 cycle, and was performed for 100 cycles, and then, the capacity retention rate, the resistance increase rate, and the volume increase rate were calculated according to the following equations 1 to 3 and are shown in the following Table 4.

[0191] [Equation 1]

[0192] Capacity retention rate (%) = (discharge capacity after 100 cycles / initial discharge capacity) × 100

[0193] [Equation 2]

[0194] Resistance increase rate (%) = {(resistance after 100 cycles - initial resistance) / initial resistance} × 100

[0195] [Equation 3]

[0196] Volume increase rate (%) = {(volume after 100 cycles - initial volume) / initial volume} × 100

[0197] [Table 4]

[0198]

[0199] The results in Table 4 above confirm that when the first additive and the second additive of the present application are included as electrolyte additives, the performance of a lithium secondary battery using 100 wt % Si as a negative electrode active material after rapid charging can be effectively improved.

[0200] Specifically, it can be confirmed that the battery of the present invention shows significantly improved results in capacity, resistance and volume after rapid charging compared to when the first additive and the second additive are not included (Comparative Example 1) and when the first additive or the second additive is used alone (Comparative Examples 2 and 3). In addition, it can be confirmed that the compound of formula Z1 used in Comparative Example 4 is not significantly effective in improving the rapid charging performance compared to the first additive of the present invention, while the compound of formula Z2 used in Comparative Example 5 makes the rapid charging performance worse. In addition, it can be confirmed that Comparative Example 6-1, which uses a mixture of SiO and graphite instead of Si as a negative electrode active material, also has a low capacity retention rate, a high resistance increase rate and a high volume increase rate after rapid charging compared to Example 1.

[0201] Meanwhile, among Examples 1 to 6, it can be confirmed that in Examples 3 and 4 where the weight ratio (W2 / W1) of the second additive to the first additive was 15 or more, the performance after rapid charge was the most excellent.

Claims

1. A lithium secondary battery, comprising: A non-aqueous electrolyte solution containing a lithium salt, an organic solvent, a first additive represented by Formula 1 below, and a second additive represented by Formula 2 below; A positive electrode containing a positive electrode active material; A negative electrode containing a negative electrode active material composed of silicon; and A separator disposed between the positive electrode and the negative electrode; [Formula 1] In Formula 1, A is a heterocyclic group having 3 to 5 carbon atoms or a heteroaryl group having 3 to 5 carbon atoms, R1 is an alkylene group having 1 to 3 carbon atoms, [Formula 2] In Formula 2, R2 is an alkyl group having 1 to 10 carbon atoms substituted with one or more fluorines.

2. The lithium secondary battery according to claim 1, wherein A in Formula 1 is a nitrogen-containing heteroaryl group having 3 to 5 carbon atoms.

3. The lithium secondary battery according to claim 1, wherein R2 in Formula 2 is -(CR2) n CF3; R is hydrogen or fluorine; and n is an integer from 0 to 9.

4. The lithium secondary battery according to claim 1, wherein Based on the total weight of the non-aqueous electrolyte solution, the content of the first additive is 0.05 wt% to 10 wt%.

5. The lithium secondary battery according to claim 1, wherein Based on the total weight of the non-aqueous electrolyte solution, the content of the second additive is 0.1 wt% to 15 wt%.

6. The lithium secondary battery according to claim 1, wherein The weight ratio of the second additive to the first additive is 1.5 or more.

7. The lithium secondary battery according to claim 1, wherein The weight ratio of the second additive to the first additive is 6 or more.

8. The lithium secondary battery according to claim 1, wherein The non-aqueous electrolyte solution further contains one or more third additives selected from the group consisting of vinylene carbonate, 1,3-propane sultone, 1,3-propene sultone, and lithium difluorophosphate.

9. The lithium secondary battery according to claim 1, wherein: The organic solvent contains a mixture of a fluorinated cyclic carbonate solvent and a chain carbonate solvent.

10. The lithium secondary battery according to claim 9, wherein: The chain carbonate solvent includes diethyl carbonate, ethyl methyl carbonate, or a mixture thereof.

11. The lithium secondary battery according to claim 1, wherein In the mixed solution of the lithium salt and the organic solvent, the concentration of the lithium salt is 1.5 M or more.

12. The lithium secondary battery according to claim 1, wherein The positive electrode active material contains a lithium composite transition metal oxide represented by Formula 3: [Formula 3] Li 1+x (Ni a Co b Mr c M d )O2 In Formula 3, M is one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, 1+x, a, b, c, and d are atomic fractions of each independent element, where -0.2 ≤ x ≤ 0.2, 0.60 ≤ a < 1, 0 < b ≤ 0.30, 0 < c ≤ 0.30, 0 ≤ d ≤ 0.10, and a + b + c + d = 1.

13. The lithium secondary battery according to claim 1, wherein: The positive electrode active material contains a lithium composite transition metal oxide, and in the lithium composite transition metal oxide, the molar ratio of nickel in the transition metal is 70 mol% or more.

Citation Information

Patent Citations

  • Semiconductor device and semiconductor package

    KR1020220087179A

  • Composition for prevention, improvement or treatment of cognitive dysfunction comprising mixture of Humulus japonicus leaf extract, Diospyros lotus leaf extract, Zingiber officinale extract and red zinger extract as effective component

    KR1020230087210A